Breaking the resilience of a two-dimensional Bose-Einstein condensate to fragmentation - Klaiman, Shachar; Lode, Axel U. J.; Streltsov, Alexej Iwanowitsch; Cederbaum, Lorenz S.; Alon, Ofir E. (Physical review. A, Atomic, molecular, and optical physics, 2014)
A two-dimensional Bose-Einstein condensate (BEC) split by a radial potential barrier is investigated. We determine on an accurate many-body level the system's ground-state phase diagram as well as a time-dependent phase diagram of the splitting process. Whereas the ground state is condensed for a wide range of parameters, the time-dependent splitting process leads to substantial fragmentation. We demonstrate the dynamical fragmentation of a BEC despite its ground state being condensed. The results are analyzed using a mean-field model and suggest that a large manifold of low-lying fragmented excited states can significantly impact the dynamics of trapped two-dimensional BECs.